Traumatic spinal cord injury in Victoria, 2007–2016. Issue 8 (5th May 2019) - Beck, Ben; Cameron, Peter A; Braaf, Sandra; Nunn, Andrew; Fitzgerald, Mark C; Judson, Rodney T; Teague, Warwick J; Lennox, Alyse; Middleton, James W; Harrison, James E; Gabbe, Belinda J
Abstract: Objective: To investigate trends in the incidence and causes of traumatic spinal cord injury (TSCI) in Victoria over a 10‐year period. Design, setting, participants: Retrospective cohort study: analysis of Victorian State Trauma Registry (VSTR) data for people who sustained TSCIs during 2007–2016. Main outcomes and measures: Temporal trends in population‐based incidence rates of TSCI (injury to the spinal cord with an Abbreviated Injury Scale [AIS] score of 4 or more). Results: There were 706 cases of TSCI, most the result of transport events (269 cases, 38%) or low falls (197 cases, 28%). The overall crude incidence of TSCI was 1.26 cases per 100 000 population (95% CI, 1.17–1.36 per 100 000 population), and did not change over the study period (incidence rate ratio [IRR], 1.01; 95% CI, 0.99–1.04). However, the incidence of TSCI resulting from low falls increased by 9% per year (95% CI, 4–15%). The proportion of TSCI cases classified as incomplete tetraplegia increased from 41% in 2007 to 55% in 2016 ( P < 0.001). Overall in‐hospital mortality was 15% (104 deaths), and was highest among people aged 65 years or more (31%, 70 deaths). Conclusions: Given the devastating consequences of TSCI, improved primary prevention strategies are needed, particularly as the incidence of TSCI did not decline over the study period. The epidemiologic profile of TSCI has shifted, with an increasing number of TSCI events in older adults. This change has implications for prevention, acute and post‐discharge care, and support.